1982
DOI: 10.1002/kin.550140512
|View full text |Cite
|
Sign up to set email alerts
|

F‐to‐HF reactions. VIII. Nonthermal complications for the CHF3/C3F6/C2F6 moderated nuclear recoil system

Abstract: Results are reported from moderated nuclear recoil I8F experiments with the 273 K CHF:+/C:,F~/CZF~ system. Although the measurement sensitivity is only about f12%, there is no evidence to support the occurrence of nonthermal F-to-HF reactions at 95 mol % CzFe moderator concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1982
1982
1984
1984

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The early 18 [132,133,135] led to relative Arrhenius parameters exhibiting good agreement with literature data [137,139,[229][230][231][232], However, the subsequent attempts to develop absolute scaling relations based upon these results have been disappointing, probably in part because of previously unanticipated 18 F loss unimolecular decomposition complications associated with the thermal 18 F + C 3 F 6 reaction at 1.32 atm [234], Although the moderated nuclear recoil method is applicable for this type of study, further 18 F experiments are needed at enhanced moderator concentrations and total pressures.…”
Section: The Present Status Of Hot Atom Research In Chemical Kineticssupporting
confidence: 55%
“…The early 18 [132,133,135] led to relative Arrhenius parameters exhibiting good agreement with literature data [137,139,[229][230][231][232], However, the subsequent attempts to develop absolute scaling relations based upon these results have been disappointing, probably in part because of previously unanticipated 18 F loss unimolecular decomposition complications associated with the thermal 18 F + C 3 F 6 reaction at 1.32 atm [234], Although the moderated nuclear recoil method is applicable for this type of study, further 18 F experiments are needed at enhanced moderator concentrations and total pressures.…”
Section: The Present Status Of Hot Atom Research In Chemical Kineticssupporting
confidence: 55%
“…The O2 concentration in each sample must either be reduced to the sub-parts-per-million level or be consistently maintained in excess of 2.0 mol-%. The fluorocarbon and CH4 reagents have been purified from impurity 0 2 using repeated 77 K freeze-pump-thaw cycles and Cs gettering, respectively Kinetic complications resulting from the presence of reactive impurities in the C2F6 become important in 18F MNR experiments at large moderator concentrations [17]. Because C2F6 concentrations as large as 99.95 mol-% have been used in this study, several precautions in addition to routine vacuum degassing have been observed to ensure the quality of the C2F6 reagent.…”
Section: Methodsmentioning
confidence: 99%
“…Because our measurement techniques have been described in companion papers [4,17,18], the following account has been limited to the preparation of high-pressure samples containing CH4 thermal competitor.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations